(untitled) - Sun, Meng (Bio-Protocol)

An Image-based Dynamic High-throughput Analysis of Adherent Cell Migration (Bio Protoc)

(untitled)
In this protocol, we describe a method to monitor cell migration by live-cell imaging of adherent cells. Scratching assay is a common method to investigate cell migration or wound healing capacity. However, achieving homogenous scratching, finding the optimal time window for end-point analysis and performing an objective image analysis imply, even for practiced and adept experimenters, a high chance for variability and limited reproducibility. Therefore, our protocol implemented the assessment for cell mobility by using homogenous wound making, sequential imaging and automated image analysis. Cells were cultured in 96-well plates, and after attachment, homogeneous linear scratches were made using the IncuCyte ( ® ) WoundMaker. The treatments were added directly to wells and images were captured every 2 hours automatically. Thereafter, the images were processed by defining a scratching mask and a cell confluence mask using a software algorithm. Data analysis was performed using the IncuCyte ( ® ) Cell Migration Analysis Software. Thus, our protocol allows a time-lapse analysis of treatment effects on cell migration in a highly reliable, reproducible and re-analyzable manner.